2022
DOI: 10.1101/2022.07.21.500524
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-nucleus resolution mapping of the adult C. elegans and its application to elucidate inter- and trans-generational response to alcohol

Abstract: Single-cell RNA transcriptomic platforms have significantly contributed to our understanding of tissue heterogeneity as well as of developmental and cellular differentiation trajectories. They also provide an opportunity to map an organism’s response to environmental cues with high resolution and unbiasedly identify the cell types that are the most transcriptionally sensitive to exposures. Here, we applied single nucleus RNA-seq experimental and computational approaches to C. elegans to establish the transcrip… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Its transparency and spatially distinct meiotic stages allow for the direct visualization and easy identification of meiotic stages and meiotic defects. We previously showed that this model can be leveraged for the dissection of reproductive toxicity mechanisms as demonstrated in the context of a variety of environmental exposures such as endocrine disruptors 9,10 , metals 11 , pesticides 12 , or alcohol 13 . We also showed that genetic tools developed to identify new genes and pathways implicated in germ cell differentiation can be applied for the rapid identification of mammalian reproductive toxicants 12,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Its transparency and spatially distinct meiotic stages allow for the direct visualization and easy identification of meiotic stages and meiotic defects. We previously showed that this model can be leveraged for the dissection of reproductive toxicity mechanisms as demonstrated in the context of a variety of environmental exposures such as endocrine disruptors 9,10 , metals 11 , pesticides 12 , or alcohol 13 . We also showed that genetic tools developed to identify new genes and pathways implicated in germ cell differentiation can be applied for the rapid identification of mammalian reproductive toxicants 12,14,15 .…”
Section: Introductionmentioning
confidence: 99%